Longitudinal associations between the COVID-19 pandemic and sleep characteristics in children and parents - Wernecke, Deborah; Peter, Raphael S.; Braig, Stefanie; Zarco, Maricruz; Genuneit, Jon; Rothenbacher, Dietrich (Frontiers in Public Health, 2025)
IntroductionThe COVID-19 pandemic and associated preventive measures influenced family health and behavior, leading to diverse effects on sleep.MethodsThis study examined sleep characteristics before, during and after the COVID-19 pandemic in children (n = 558), mothers (n = 465), and fathers (n = 318) in Germany, using data from the prospective Ulm SPATZ Health Study. We compared the period from April 2017 to May 2023 (children aged 5–10 years) with the period from 15 March 2020 to 3 April 2022, defined as “COVID-19 pandemic.” Sleep quality was measured using the Children's Sleep Habits Questionnaire (CSHQ) and the Pittsburgh Sleep Quality Index (PSQI), among children and parents, respectively. Multivariable mixed models were used to assess the associations of the COVID-19 pandemic compared to before and after the pandemic with sleep characteristics among boys, girls, mothers, and fathers, separately.ResultsChild and parent sleep quality showed a weak correlation among 6-year-old boys and their mothers. A moderate correlation was observed between mothers' mental health and boys' sleep quality at ages 5, 6, and 9. Parents' mental health showed a moderate correlation with their sleep quality. Multivariable mixed models revealed better sleep quality (lower CSHQ total scores) among boys during the COVID-19 pandemic compared to before and after. Daytime sleepiness decreased among boys and girls, while no significant changes were found for sleep duration and sleep latency. Among mothers, sleep duration increased on free-days, while fathers experienced increased sleep duration on work-days, along with increased sleep efficiency.DiscussionThis study showed that family sleep quality (indexed with the CSHQ and PSQI) did not decrease during the COVID-19 pandemic compared to sleep quality measured at one (parents) or two (children) annual time points before the pandemic and up to one after it. Instead, parental sleep duration increased, children experienced reduced daytime sleepiness, and boys exhibited improved sleep quality. To effectively optimize public health during a pandemic, findings on sleep quality should be interpreted in conjunction with findings on mental health, given their interrelated nature, as also indicated by our study.